Proses Pendampingan Hukum oleh YLBH Laskar Sabilillah Indonesia terhadap Korban Kekerasan dalam Rumah Tangga (KDRT) di Kabupaten Ungaran - Irawan, Candra Wahyu; Santoso, Aris Prio Agus (Eastasouth Institute, 2025)
This study examines the legal assistance process provided by the Indonesian Legal Aid Foundation (YLBH) Laskar Sabilillah to victims of Domestic Violence (KDRT) in Ungaran Regency, as well as the challenges and strategies involved in its implementation. Using field observation, in-depth interviews, and document analysis, the research found that legal assistance is delivered comprehensively through both litigation and non-litigation approaches, including free legal consultations, risk assessments, psychosocial support, legal document preparation, and victims’ economic empowerment. The main challenges identified include victims’ low legal awareness, emotional attachment and economic dependence on perpetrators, severe trauma, lack of supporting documents, and structural barriers such as poor inter-agency coordination and limited institutional resources. To address these challenges, YLBH employs community-based strategies, strengthens advocacy networks, conducts legal education, and engages volunteer psychologists and community leaders. The findings indicate that YLBH’s role extends beyond formal legal representation, functioning as a social change agent that fills the state’s protection gap for vulnerable groups, in line with the principles of substantive justice, non-discrimination, and social inclusion. This study underscores the importance of a multidisciplinary and gender-sensitive approach in addressing domestic violence cases and highlights the need for synergy between the state, civil society, and local actors to achieve effective legal protection.